Peningkatan Hasil Belajar Siswa dalam PAK Melalui Model Problem Based Learning (PBL) Kelas V SD Negeri 044845 Payanderket - Juita Br Tarigan; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to enhance student learning outcomes in Religious Education through the implementation of the Problem Based Learning (PBL) model at SD Negeri 044845 Payanderket. Utilizing a Classroom Action Research (CAR) approach, the research was conducted in two cycles, focusing on improving the character profile of Pancasila students. The results indicate a significant improvement in student learning outcomes, with the average score increasing from 72% in Cycle I to 80% in Cycle II. The findings suggest that the consistent application of the PBL model can effectively enhance the quality of learning and foster critical thinking skills among students. It is recommended that educators adopt PBL as a regular teaching strategy to further improve student engagement and academic performance.